Reformation Observances - Krey, Philip D. W.; Bellitto, Christopher M.; Radano, John A. (Eugene : Wipf and Stock Publishers, 2017)
The year 2017 marks the five-hundredth anniversary of the Reformation, if that event is dated from the posting of Martin Luther's Ninety-Five Theses. Admittedly, 2017 is an arbitrary and somewhat artificial milestone. Nevertheless, anniversaries can be special occasions that allow for an appreciation and evaluation of memorable persons and events. As a number of Reformation anniversaries approach, the historical significance of the Reformation merits increased attention. Employing a variety of historiographical methods from intellectual history to postcolonial theory, this volume demonstrates.
Foreword: 2017 -- an ecumenical perspective / John A. Radano -- Preface: Remembering Luther -- a reformer in church history / Christopher W. Bellitto [Christopher M. Bellitto] -- Martin Luther and the Lutheran Reformation -- October 31, 1517-October 31, 2017: from Augustinian monk and doctor of the church attempting to reform Catholic theology in 1517 to doctor communis of the church in 2017 / Philip D. W. Krey -- Martin Luther and the Episcopal Church / Robert W. Prichard -- Celebrating the dynamic legacy of the Reformation: an Indian perspective / J. Jayakiran Sebastian -- The five-hundredth anniversary of the Reformation: a Catholic perspective / Jacob W. Wood.
Description based upon print version of record.
Includes bibliographical references.
Master record variable field(s) change: 050, 072, 082, 650 - OCLC control number change
Keywords: Reformation; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books; Electronic books